2004
DOI: 10.1101/lm.77904
|View full text |Cite
|
Sign up to set email alerts
|

CB1 Cannabinoid Receptors Modulate Kinase and Phosphatase Activity During Extinction of Conditioned Fear in Mice

Abstract: Cannabinoid receptors type 1 (CB1) play a central role in both short-term and long-term extinction of auditory-cued fear memory. The molecular mechanisms underlying this function remain to be clarified. Several studies indicated extracellular signal-regulated kinases (ERKs), the phosphatidylinositol 3-kinase with its downstream effector AKT, and the phosphatase calcineurin as potential molecular substrates of extinction behavior. To test the involvement of these kinase and phosphatase activities in CB1-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 39 publications
7
95
1
2
Order By: Relevance
“…Cannich et al 288 reported upregulation in extinguished wild-type mice relative to nonextinguished controls, and interestingly, found that pMAPK actually decreased in cannabinoid receptor knockout (CB1À/À) mice that exhibit a profound impairment in extinction. Yang and Lu 173 reported a modest increase in pMAPK within the BLA in rats exposed to an extinction training protocol that was not sufficient to produce significant behavioral extinction, and a larger and statistically significant increase in rats trained with the same protocol after administration of DCS.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannich et al 288 reported upregulation in extinguished wild-type mice relative to nonextinguished controls, and interestingly, found that pMAPK actually decreased in cannabinoid receptor knockout (CB1À/À) mice that exhibit a profound impairment in extinction. Yang and Lu 173 reported a modest increase in pMAPK within the BLA in rats exposed to an extinction training protocol that was not sufficient to produce significant behavioral extinction, and a larger and statistically significant increase in rats trained with the same protocol after administration of DCS.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…290,291 Studies employing measurement of pAkt levels within the BLA following extinction training have produced very inconsistent results. Cannich et al 288 reported no significant increase in pAkt in the BLA of extinguished wild-type or cannabinoid receptor knockout (CB1À/À) mice relative to nonextinguished controls, although the ratio of pAkt levels in extinguished vs nonextinguished animals was significantly greater in the knockouts (which exhibit a profound extinction impairment) than in the wild types. Yang and Lu 173 reported a modest increase in BLA pAkt in rats following exposure to an extinction training protocol that was not sufficient to produce measurable behavioral extinction, but a significant increase in animals trained with the same protocol under the influence of DCS.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK is known to be required for several forms of synaptic plasticity and learning and memory (English and Sweatt 1997;Impey et al 1998;Atkins et al 1998;Coogan et al 1999;Schafe and LeDoux 2000). In the mPFC, the phosphorylated level of ERK44 was significantly increased after extinction training (Cannich et al 2004). Infusion of ERK inhibitor into the mPFC immediately after extinction training blocked extinction, suggesting the requirement of ERK activation in the behavioral process of extinction (Hugues et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The samples were treated as previously described [24] . Loading buffer (16% glycerol, 20% β-mercaptoethanol and 0.05% bromophenol blue) was added to each sample (3:1, sample/ loading buffer) before boiling for 3 min.…”
Section: Western Blot Assaysmentioning
confidence: 99%